Large Language Models (LLMs) as A Tool for Supporting Communication in Operational Management Information Systems and in Industry 4.0 Supply Chains - Michał Fertsch; Marek FERTSCH (Communications of International Proceedings, 2025)
A large language model is a language model with massive parameters that undergoes pretraining tasks (e.g., masked language modeling and autoregressive prediction) to understand and process human language by modeling the contextualized text semantics and probabilities from large amounts of text [Y. Yao at all. 2024]. This article considers the possibility of using large language systems as communication support tools in IT systems for operational management and in Industry 4.0 supply chains. The conditions that must be met and the limitations that may arise when using large language models in IT systems supporting the management of manufacturing and service enterprises and supply chains will be identified. Particular attention will be paid to the conditions and requirements created by IT systems in enterprises and Industry 4.0 supply chains. The concept of incorporating large language models into the IT systems of these organizations will be outlined.
Keywords: Large Language Models (LLMs); Artificial Intelligence; Communication Support; Cyber-Physical Systems